DEVELOPMENT AND CHARACTERIZATION OF ORAL SWELLABLE RAPID RELEASE FILM WITH SUPERDISINTEGRANT-SURFACTANT - IMTIAZ, NEHA; MAJEE, SUTAPA BISWAS; BISWAS, GOPA ROY (International Journal of Current Pharmaceutical Research, 2021)
Objective: Oral disintegrating films consisting of hydrophilic polymer are designed to be quickly hydrated by saliva, adhere to the mucosa and disintegrate rapidly to release the drug. The aim of the present study was to prepare stable, flexible swellable rapid release oral films with hydroxypropyl methylcellulose E15 LV (HPMC) and polyvinyl alcohol (PVA) in different ratios. Guar gum was incorporated as the mucoadhesive agent. In order to achieve rapid disintegration of the film cross carmellose sodium (superdisintegrant) and surfactant like Tween 80 were added. The model drug used in the study was diclofenac sodium. Methods: Films were developed using HPMC E15 LV and PVA by solvent casting method and characterized for thickness, swelling index, disintegration time, folding endurance, drug content, and in vitro drug release pattern and kinetics. Results: The prepared swellable rapid release oral films were quite flexible and transparent with a smooth texture. The swelling index study confirmed that the films possessed the desired swelling property. Fastest disintegration was observed with the oral film containing HPMC: PVA in the ratio of 2:1, guar gum at 120 mg, 20% w/w crosscarmellose sodium and 4%w/w Tween 80. The swellable rapid release oral films were found to follow either Higuchi or Korsmeyer-Peppas model with drug release following either Fickian or non-Fickian diffusion. Maximum drug release of around 70% was observed from the above-mentioned film in 1hr in simulated salivary fluid. Conclusion: Therefore, swellable rapid release oral films with HPMC E15 LV: PVA, guar gum, croscarmellose sodium and Tween 80 demonstrated satisfactory swelling, rapid disintegration and improved drug release for oromucosal absorption.